Telemedicine Public Reimbursement Models for National and Subnational Jurisdictions: Scoping Review - Evan Huang-Ku; Panchanok Muenkaew; Kinanti Khansa Chavarina; Yin May Tun; Zin Nwe Win; Wanrudee Isaranuwatchai; Saudamini Vishwanath Dabak; Natasha Howard (Journal of Medical Internet Research)
Abstract BackgroundTelemedicine has transformed health care delivery, offering improved access, efficiency, and potentially cost-effectiveness. However, wide-scale implementation is challenged due to multiple factors. Among these, reimbursements were reported to influence the scalability and sustainability of telemedicine. ObjectiveThis study aimed to examine current payment models and reimbursement coverage for telemedicine in any national and subnational jurisdictions to inform the development of reimbursement policy. MethodsWe conducted a scoping review using Arksey and O’Malley’s 6-stage method, including sources that discussed telemedicine payment methods reimbursed by public payers. To supplement the limited results, particularly from low- and middle-income countries in Asia, we conducted 5 stakeholder interviews with telemedicine providers or those with experience in telemedicine reimbursement models who added insights for India, Nepal, and Taiwan. Data were synthesized narratively. ResultsWe included 31 of 14,522 records screened. Most (n=22, 71%) records were published after 2020, were research studies (n=26, 84%), and discussed reimbursement in the United States (n=24, 77%). We categorized reimbursement coverage as the purpose of telemedicine, health conditions, patients’ nonhealth conditions, service providers, interaction participants, interaction modes, and technology used. Payment methods varied widely and included fee-for-service, capitation, bundled payment, and value-based models. Varying telemedicine reimbursement models adopted by countries reflect health service and care objectives along with health system characteristics. Payment mechanisms were linked to telemedicine services or broader health care delivery, with each presenting unique advantages. ConclusionsWorkable telemedicine reimbursement is a critical enabling factor in expanding health care access by incentivizing provider participation, ensuring financial sustainability, promoting equity in access, and aligning telemedicine with broader health goals. This review provides a starting point for countries in designing a telemedicine reimbursement model specific to population needs and health system capacity. Policy makers are encouraged to leverage these insights in adapting telemedicine reimbursement to their context.